Peer-to-peer non-line-of-sight localization in multipath environment - Wen, Kai (2015)
Current localization schemes are able to locate a mobile device using Time-of- Arrival (TOA) and Angle-of-Arrival (AOA) information measured at both the mobile device and reference device. This information is used to derive line of possible mobile device position (LPMD). The intersection points of LPMDs are used to estimate mobile position. However these algorithms do not work well in a dense multipath environment with high level of TOA and AOA noises. In addition, these techniques require at least two paths to locate the mobile position. This paper presents novel methods to find the area of mobile device position and a least square estimator is constructed to find the centroid of mobile position. Furthermore, the proposed technique is able to determine mobile device using one LOS path. Simulation results show that our proposed scheme outperforms previous bidirectional localization schemes by a significant margin especially at high levels of TOA and AOA measurement noise.